The long-term preservation of the digital heritage: the case of universities institutional repositories - Luciana Duranti (JLIS.it, 2010)
The article faces the problems related to long-term preservation of the digital archives content. Archival material requires a special attentio due to credibility, juridical value, moral and legal rights, and privacy. The need to ensure accessibility and integrity of informatic data is a problem that involves all aspects and fields of informatization, and it is closely related to metadata choice and duplication. Through the analysis of the case-study represented by cIrcle, the istitutional digital repository della University of British Columbia (UBC), the article shows problems, risks, and solutions in managing a digital archive, showing that the professional experience of archivists can be useful in order to develop technological systems for non-archivistic contents.